Sliding malar bone augmentation technique with a high le fort I surgically assisted rapid maxillary expansion - DERGİN, GÜHAN; BİREN, SİBEL (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2017)
The purpose of this report is to evaluate the effectiveness of a high Le Fort I osteotomy design, including the malar bones, which allows segment sliding over the zygoma and forces the osteotomized segment to move forward with distraction. Two patients (male, 23-and 30-year-old) with malar deficiency underwent high Le Fort I osteotomy and surgically assisted rapid maxillary expansion procedure was followed. Records were taken before and 6 months after surgery for comparison, including intra and extra oral photographs and three-dimensional cone-beam computed tomography (CBCT) images. The bone malar width and bone malar depth changings in malar region were evaluated. Preoperative and postoperative CBCT images and clinical views of the patients showed forward movement of the malar region.
Keywords: Cone-beam computed tomography; malar deficiency; malar depth; malar width; surgically assisted rapid maxillary expansion; SOFT-TISSUE CHANGES; OSTEOTOMY